2000
DOI: 10.1144/gsl.sp.2000.179.01.23
|View full text |Cite
|
Sign up to set email alerts
|

Syn-convergent high-temperature metamorphism and magmatism in the Variscides: a discussion of potential heat sources

Abstract: A period of pervasive high-temperature metamorphism and igneous activity from 340 to 325 Ma is a well-established characteristic of the Variscan Orogen of Central Europe. During this stage, the internal zone of the orogen was virtually soaked by granitic to granodioritic magmas. Petrological data point to temperatures of 600-850 ~ at upper-to mid-crustal levels. These elevated temperatures occurred during the final convergence stage and may be comparable with similar processes inferred from geophysical evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 60 publications
0
45
0
1
Order By: Relevance
“…These facts are clearly at variance with models that designate collisional crustal thickening and radiogenic heat production as the main reasons for granite magma formation in the south-western Bohemian Massif. Since late Variscan subduction models have turned out to be unlikely for the Bohemian Massif (Franke 2000), we hold the view that a process of post-collisional delamination of lithospheric mantle (Bird 1979;Houseman et al 1981;Henk et al 2000) can probably best explain the plutonic phenomena observed in the SDGB.…”
Section: In Search Of a Tectonic Scenariomentioning
confidence: 72%
See 1 more Smart Citation
“…These facts are clearly at variance with models that designate collisional crustal thickening and radiogenic heat production as the main reasons for granite magma formation in the south-western Bohemian Massif. Since late Variscan subduction models have turned out to be unlikely for the Bohemian Massif (Franke 2000), we hold the view that a process of post-collisional delamination of lithospheric mantle (Bird 1979;Houseman et al 1981;Henk et al 2000) can probably best explain the plutonic phenomena observed in the SDGB.…”
Section: In Search Of a Tectonic Scenariomentioning
confidence: 72%
“…Zwart & Dornsiepen 1980;Henk et al 2000). Various tectonic scenarios have been invoked to explain it.…”
Section: In Search Of a Tectonic Scenariomentioning
confidence: 99%
“…The style of orogenic collapse of the French Massif Central has been compared with that of the Tibetan plateau and the Basin and Range province (Mattauer et al 1988; Ménard and Molnar 1988). The geodynamic processes responsible for the cessation of contractional deformation and the onset of orogenic collapse in the Variscides, however, are still the subject of much interest and the roles of slab detachment, delamination and convective removal of the mantle lithosphere remain hotly debated (e.g., Schaltegger 1997;Zulauf 1997a;Thompson et al 1997;Willner et al 2002;Bruguier et al 2003;Schott and Schmeling 1998;Henk et al 2000;Arnold et al 2001;Schulmann et al 2002Schulmann et al , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The viable possibilities include lithospheric thinning in a back-arc region, or asthenospheric mantle upwelling due to slab break-off or ridge subduction and slab window formation (Davies and von Blanckenburg 1995;Thorkelson 1996;Henk et al 2000).…”
Section: Granite Suitementioning
confidence: 99%